Pemikiran futurulogis kejawen dalam Jangka Jayabaya - Purwadi, Purwadi (Kejawen, 2025)
Kediri Kingdom is very well-known in our national history. So that its influence to nowadays life as a reference for common people to respond contemporary phenomena. Sometimes, the marginal, poor and in vain people memorize the winning times of Kediri Kingdom. The myth of ratu adil represents by Prabu Jayabaya is so sound in Javanese thought. Prabu Jayabaya's predictions often become reference to analyze contemporary situations. When there is a riot, people refer to Jayabayas prediction without observing whether the prediction is right from Jayabaya or not. At certain times, Jayabayas grave in Mamenang, Kediri, often visited by people with various aims. Those people believe that Prabu Jayabaya is able to understand their grief. They, even, ask for his pray in order to make their wishes come true.